Analysis of Speech Disorder “Stuttering” in the Character Glenn in the Film Mendarat Darurat: A Psycholinguistic Study - Walian, Fazra Oktaviana (BRIN Publishing (Penerbit BRIN), 2025)
This study aims to analyze the representation of the speech disorder “stuttering” experienced by the character Glenn in the film Mendarat Darurat through a psycholinguistic approach. The data collection technique employed is in-depth observation of relevant scenes, along with transcription of Glenn’s stuttered dialogues. The research method applied is descriptive qualitative, which explains the phenomenon by describing the characteristics of the subject under study without applying any experimental treatment. The descriptive qualitative procedure includes data collection, data organization, and data interpretation. The data analysis technique used is the interactive analysis model by Miles and Huberman, which involves three main steps: data reduction, data display, and conclusion drawing/verification. The data analyzed in this study consist of dialogues containing stuttering, with the data source being the film Mendarat Darurat. The analysis results indicate that there are 18 excerpts/dialogues that influence both the character’s speech and behavior, offering insights into how speech disorders are represented in film media. It is hoped that the findings of this study will contribute to the understanding of speech disorder representations in media and their impact on audience perception.